Biochemical aspects of Huntington's chorea. Issue 6 (June 1977) - Caraceni, T; Calderini, G; Consolazione, A; Riva, E; Algeri, S; Girotti, F; Spreafico, R; Branciforti, A; Dall'olio, A; Morselli, P L
Abstract : Fifteen patients affected by Huntington's chorea were divided into two groups, 'slow' and 'fast', according to IQ scores on the Wechsler-Bellevue scale, and scores on some motor performance tests. A possible correlation was looked for between some biochemical data (cerebrospinal fluid (CSF), homovanillic acid (HVA), and 5-hydroxyindolacetic acid (5HIAA) levels, plasma dopamine-beta-hydroxylase (DBH), dopamine (DA) uptake by platelets), and clinical data (duration of illness, severity of symptoms, age of patients, IQ scores, 'slow' and 'fast' groups). The CSF, HVA, and 5HIAA levels were found to be significantly lowered in comparison with normal controls. DBH activity and DA uptake by platelets did not differ significantly from normal subjects. Treatment with haloperidol in all patients and with dipropylacetic acid in three patients did not appear to modify the CSF, HVA, and 5HIAA concentrations, the plasma DBH activity, or the DA uptake. There were no significant differences in the CSF, HVA, and 5HIAA contents between the two groups of patients, and there was no correlation between biochemical data and clinical features.